Implication of anthropometric profile and alimentary consumption on risk for diseases among school children in the 1st to 4th grades - Vanessa Monteiro; Graciette Matioli (Universidade de São Paulo, 2010)
This study aimed to determine the anthropometric profile and diet of 652 school children from the 1st to 4th grades of elementary education in six private schools in the city of Maringá, Paraná, Brazil. Children's weight and height were classified according to the Body Mass Index proposed by Must et al. (1991). Food consumption was evaluated by means of a questionnaire about daily food frequency. Statistical analysis was carried out using linear and logistic regression tests, with a significance level of 5%. High rates of overweight and obesity, 21.9% and 13.3% respectively, were observed, which did not show a significant relationship with total food consumption. The data obtained were: high consumption of foods rich in energy, such as sugar- and fat-rich foods, and insufficient consumption of low-energy foods that are sources of micronutrients, such as vegetables. It is necessary to enhance the promotion of good alimentary and health habits within schools to lower risk factors for developing diseases, as well as to develop and validate a questionnaire to reliably assess the diet of the infant population. Este trabalho objetivou determinar o perfil antropométrico e o consumo alimentar entre escolares de 1ª a 4ª séries do ensino fundamental de escolas privadas de Maringá - PR. A amostra de estudo foi de 652 alunos. Verificou-se o peso e a estatura e classificados de acordo com o Índice de Massa Corporal proposto por Must et al. (1991). O consumo alimentar foi avaliado por meio de um questionário de freqüência alimentar diária. A análise estatística foi realizada pelos testes de associação e regressão logística linear, com nível de significância de 5%. Verificaram-se índices altos de sobrepeso e obesidade, 21,9% e 13,3%, respectivamente, os quais não mostraram relação significativa com o consumo alimentar. Os dados obtidos foram: alto consumo de alimentos ricos em energia, como aqueles ricos em açúcares e gorduras, e um consumo insuficiente de alimentos pouco energéticos e fonte de micronutrientes, como os vegetais. Para diminuir os fatores de risco do desenvolvimento de doenças faz-se necessário o aumento da promoção de bons hábitos alimentares e saúde dentro das escolas, além da necessidade de elaborar e validar um questionário de consumo alimentar para avaliar a população infantil.